A business plan for a 600-acre farm & 300-head commercial cow herd in south central Idaho - Staley, Joshua (Kansas State University, 2010)
This thesis was written for the purpose of looking at the feasibility of operating a prospective business; a farm and ranch in southern Idaho. For practical reasons, I looked at a specific farm consisting of 600 irrigated acres, which are irrigated via 5 center pivots. Attached to the farm is an additional 400 acres of pasture ground seeded to crested wheat. In conjunction with operating the farm, I examined the feasibility of leasing a 300 head commercial cow herd from a separate owner than the land owner. Summer pasture for the cows would be leased from a grazing association located in northern Nevada and winter feed would come from the farm pasture, crop aftermath located on the farm, and corn stalks from a neighboring farm. Crops looked at being produced were grain corn and alfalfa hay. Operating cost projections were made using current market values, while the price received for each commodity is based on ten-year historical prices. Historical prices were used to determine whether the business is viable in the long-run. Rent on the farm is based on a 60/40 percent crop share of which the land owner’s share is 40 percent. Lease payment for the cow herd is based on a 2/3, 1/3 calf crop split of which the cow owner’s share is 1/3 of the calf crop. After analyzing the operation’s financials the business is not feasible.
Keywords: Business Planning; Production Agriculture; Agriculture, General (0473); Business Administration, Management (0454); Economics, Agricultural (0503)